Antipsychotic augmentation vs. monotherapy in schizophrenia: systematic review, meta‐analysis and meta‐regression analysis - Galling, Britta; Zink, Mathias (World psychiatry, 2017)
Antipsychotic polypharmacy in schizophrenia is much debated, since it is common and costly with unclear evidence for its efficacy and safety. We conducted a systematic literature search and a random effects meta‐analysis of randomized trials comparing augmentation with a second antipsychotic vs. continued antipsychotic monotherapy in schizophrenia. Co‐primary outcomes were total symptom reduction and study‐defined response. Antipsychotic augmentation was superior to monotherapy regarding total symptom reduction (16 studies, N=694, standardized mean difference, SMD=–0.53, 95% CI: −0.87 to −0.19, p=0.002). However, superiority was only apparent in open‐label and low‐quality trials (both p<0.001), but not in double‐blind and high‐quality ones (p=0.120 and 0.226, respectively). Study‐defined response was similar between antipsychotic augmentation and monotherapy (14 studies, N=938, risk ratio = 1.19, 95% CI: 0.99 to 1.42, p=0.061), being clearly non‐significant in double‐blind and high‐quality studies (both p=0.990). Findings were replicated in clozapine and non‐clozapine augmentation studies. No differences emerged regarding all‐cause/specific‐cause discontinuation, global clinical impression, as well as positive, general and depressive symptoms. Negative symptoms improved more with augmentation treatment (18 studies, N=931, SMD=–0.38, 95% CI: −0.63 to −0.13, p<0.003), but only in studies augmenting with aripiprazole (8 studies, N=532, SMD=–0.41, 95% CI: −0.79 to −0.03, p=0.036). Few adverse effect differences emerged: D2 antagonist augmentation was associated with less insomnia (p=0.028), but more prolactin elevation (p=0.015), while aripiprazole augmentation was associated with reduced prolactin levels (p<0.001) and body weight (p=0.030). These data suggest that the common practice of antipsychotic augmentation in schizophrenia lacks double‐blind/high‐quality evidence for efficacy, except for negative symptom reduction with aripiprazole augmentation.